Schoolchildren of the COVID-19 pandemic : impact and opportunities - Ceglie, Rob J., 1972-; Abernathy, Dixie F., 1964-; Thornburg, Amy W., 1973- (Emerald Publishing Limited, 2022)
The Covid pandemic is still very current and real, with many countries around the world still grappling with how to move forward. While the generation of "Covid children" will remain always as a unique cohort, there is no doubt that the results and repercussions of this most unusual experience will have implications that are far-reaching and of consequence to us all. In the United States, families and society appear to be gradually returning to some semblance of tradition, but the short and long term impact of what we have just collectively experienced, and specifically, what this experience has meant to our children, is yet to be explored or realized. This timely book explores the many facets for how the Covid-19 pandemic has impacted children in the United States. The authors explore both learning and teaching, and the social and emotional impacts felt by the pandemic. Exploring topics such as online learning, mental health, physical health, family impacts, and with a focus on detailing lessons learned, this volume is vital reading for educators and researchers alike.